Artificial Intelligence for Multisource Geospatial Information - Gloria Bordogna; Cristiano Fugazza (ISPRS International Journal of Geo-Information, 2022)
The term Geospatial Artificial Intelligence (GeoAI) is quite cumbersome, and it has no single, shared definition [...]